Reassessing the HMS Challenger collection as a late 19th century surface ocean indicator using X-ray micro-computed tomography - Stergios D. Zarkogiannis; Thomas J. Wood; C. Giles Miller; Stephen Stukins; Brett Clark (Frontiers in Marine Science)
Plankton tow net samples collected during the HMS Challenger expedition (1872–1876) have highlighted the potential to provide an unique window into past oceanic conditions. This study aims to assess the suitability of HMS Challenger sediment samples as indicators of late 19th century surface oceanic conditions using X-ray micro-computed tomography (μCT). We used μCT to examine all 21 available Challenger samples from the global ocean that were labelled as ‘tow-net at dredge’, ‘weights’, or ‘trawl’. Our analysis reveals that most samples contain benthic foraminifera shells, along with high concentrations of foraminiferal fragments and detrital quartz grains, while the remaining samples consist of sedimentary material devoid of calcareous microfossils. These findings suggest that these tow-net samples include resuspended bottom sediments rather than exclusively surface-derived material. This distinction is critical because it demonstrates that two types of Challenger tow-net samples exist: surface ocean samples and deep-water tow-net samples that incorporate seafloor material. The surface tow-net samples were recently located and are referenced in this study. These findings highlight the importance of re-evaluating historical sediment collections with modern analytical techniques to ensure accurate paleoceanographic interpretations. Furthermore, the study demonstrates the effectiveness of μCT as a non-destructive tool for sediment analysis, allowing for the detailed examination of collections without the need for washing or wet sieving.